Paraeducators: An Important Member of Educational Team for Students with Disabilities - Douglas, Sarah N.; Bowles, Ryan P.; Kammes, Rebecca (Journal of the American Academy of Special Education Professionals, 2022)
Paraeducators are an important member of the educational team for many students with disabilities. However, the perspectives of team members (principals, teachers, paraeducators) related to paraeducator supports and team roles has not been adequately explored in the literature. An online questionnaire was used within this study to examine the perceptions of elementary level team members related to paraeducator supports. Participants were recruited across one midwestern state with representation from urban, suburban, town, and rural schools. Quantitative data were analyzed using descriptive statistical methods and qualitative data were analyzed using content analysis. Results highlight team roles related to paraeducators including paraeducator training and supervision, evaluation, and paraeducator work conditions. Findings indicate many commonalities in principal, teacher, and paraeducator perspectives, but important areas of divergence. Implications for policy and practice, limitations, and future research directions are discussed.